Hubungan Karakteristik Pasien dengan Tingkat Kepuasan Pasien pada Praktik Mandiri Terapis Gigi dan Mulut di Desa Pedungan Kecamatan Denpasar Selatan - Ratmini, Ni Ketut; Artawa, I Made Budi; Nuratni, Ni Ketut; Wirata, I Nyoman (Jurnal Kesehatan Gigi (Dental Health Journal), 2025)
Health services are a form of effort carried out individually or in groups, which aims to maintain and improve health, one important indicator in assessing the quality of health services is the level of patient satisfaction with the services provided by health facilities. Patient satisfaction is a very important aspect in assessing the quality of health services, by comparing reality and expectations. The purpose of this study was to determine the relationship between patient characteristics and the level of patient satisfaction with dental and oral health services in independent dental and oral therapist practices in Pedungan Village. This research method is a quantitative study with a survey method. The number of respondents in this study was 30 people. The results showed that there was a significant relationship between the level of education and the level of patient satisfaction with dental health services provided by Dental and Oral Therapy and there was no relationship between the age and gender of the patient and the level of patient satisfaction with dental health services provided by Dental and Oral Therapy in an independent clinic in Pedungan Village, South Denpasar District. Based on this study, it can be concluded that there is a significant relationship between the level of education and the level of satisfaction with dental health services.